DAYA ANTIFUNGAL DEKOK KAYU MANIS (Cinnamomum burmanni) TERHADAP Candida Albicans SECARA IN VITRO - Rachma, Lailia Nur (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2012)
Candida albicans is the most oportunis fungi that cause flour albus. Cinnamomum burmanni have been widely known as therapy for flour albus. This efect caused by its chemical compound such as cinnamaldehyde, eugenol, cinnamic acid, limonene, cathecin, coumarin, linalool, and tannin. This research aims was to know the comparison of antifungal potency of Cinnamomum burmanni on Candida albicans in vitro. The design was true experimental. The decoction concentrations of Cinnamomum burmanni that were used were 8%, 4%, 2%, 1%, 0.5%, 0.25%, and 0.125% with three time repetition. The data was analized with One-way ANOVA test with convidence interval 95% (p 0.05). One-way ANOVA test gave result Cinnamomum burmanni had antifungal potency against Candida albicans. Minimum Inhibitory Concentration (MIC) of Cinnamomum burmanni was 1%. Minimum Fungicidal Concentration (MFC) of Cinnamomum burmanni was 2%. The conclusion was Cinnamomum burmanni had antifungal potency against Candida albicans in vitro.